Empathic Communication and Behavioral Change in Stunting Prevention by Family Assistance Teams - Leylia Khairani; Rahmanita Ginting; Fitra Ramadhani (PERSPEKTIF, 2026)
This study examines how empathic interpersonal communication practiced by Family Assistance Teams (TPK) contributes to stunting prevention in Labuhanbatu Utara District, Indonesia. Using a qualitative case study design grounded in Interpersonal Communication Theory and the Communication for Development (C4D) approach, data were collected through in-depth interviews, participatory observation, and focus group discussions with TPK cadres, families at risk of stunting, and local policymakers. The findings demonstrate that empathic communication characterized by openness, responsiveness, and emotional sensitivity plays a critical role in fostering parental behavioral change related to child nutrition and health. Home visits, interpersonal dialogue, and the use of everyday language enhance families’ understanding and acceptance of healthy practices by strengthening trust and reducing resistance. However, the effectiveness of these practices is constrained by geographical barriers, social stigma, and limited communication training among cadres. This study’s main contribution lies in highlighting empathic interpersonal communication as a key behavioral-change mechanism within community-based stunting prevention, reinforcing C4D as a practical framework for advancing Indonesia’s zero-stunting agenda.